Voriconazole and caspofungin: new antifungal drugs - Paluszewska, Monika (Contemporary Oncology/Współczesna Onkologia, 2004)
The incidence of invasive fungal infections in immunocompromised patients has increased significantly during the past 20 years because of the introduction of aggressive anticancer-chemotherapy regimens, stem cell transplantation and intensive supportive procedures (e.g. central venous catheters, mechanical ventilation). Most systemic fungal infections are caused by Candida and Aspergillus species, but a growing number of less frequent fungal pathogens have been observed in recent years (e.g. Fusarium, Scedosporium). Fungal infections have become one of the leading factors contributing to morbidity and mortality in patients with hematological malignancies and solid tumors. Current treatment strategies for these infections are limited by antifungal resistance, toxicity, drug interactions, expense. Two very different antifungal drugs (voriconazole and caspofungin) have been recently introduced into antifungal therapy. Voriconazole is a new triazole agent and acts by inhibiting the synthesis of ergosterol in the fungal cell membrane. Caspofungin is the first echinocandin antifungal drug. Caspofungin inhibits β-1,3 D-glucan synthesis in the fungal cell wall. Both agents are broad-spectrum ones with efficacy against invasive Aspergillus and Candida infections. Tolerability profile of caspofungin shows a low incidence of adverse events in clinical trials. Voriconazole has three important side-effects: visual disturbances, hepatotoxicity and skin reactions. Voriconazole inhibits cytochrome CYP450 enzymes, which results in clinically significant drug reactions with other substrates of these enzymes.